Seedling Evaluation of Diploknema butyracea (Roxb.) H.J. Lam - Bahar, Nawa; Singh, V. R. R.; Sharma, Preeti (Indian Forester, 2010)
The present investigation was carried out on seedlings evaluation in Diploknema butyracea (Cheura) under laboratory condition. During the course of test, the nature of germination was epigeous and the normal and abnormal seedlings were observed 91 and 9 per cent respectively. Ten categories of abnormalities were also found in this species.